A Small Actively Controlled High-resolution Spectrograph Based on Off-the-shelf Components. (26th January 2021) - Jones, H. R. A.; Martin, W. E.; Anglada-Escudé, G.; Errmann, R.; Campbell, D. A.; Baker, C.; Boonsri, C.; Choochalerm, P.
Abstract: We present the design and testing of a prototype in-plane echelle spectrograph based on an actively controlled fiber-fed double-pass design. This system aims to be small and efficient with the minimum number of optical surfaces—currently a collimator/camera lens, cross-dispersing prism, grating and a reflector to send light to the detector. It is built from catalog optical components and has dimensions of approximately 20 × 30 cm. It works in the optical regime with a resolution of >70, 000. The spectrograph is fed by a bifurcated fiber with one fiber to a telescope and the other used to provide simultaneous Thorium Argon light illumination for wavelength calibration. The positions of the arc lines on the detector are processed in real time and commercial auto-guiding software is used to treat the positions of the arc lines as guide stars. The guiding software sends any required adjustments to mechanical piezo-electric actuators which move the mirror sending light to the camera removing any drift in the position of the arc lines. The current configuration using an sCMOS detector provides a precision of 3.5 milli-pixels equivalent to 4 m s −1 in a standard laboratory environment.